2006
DOI: 10.1021/je060195b
|View full text |Cite
|
Sign up to set email alerts
|

Density and Viscosity of Aqueous Solutions of (N-Methyldiethanolamine + Piperazine) and (2-Amino-2-methyl-1-propanol + Piperazine) from (288 to 333) K

Abstract: The densities and viscosities of aqueous blends of piperazine (PZ) with N-methyldiethanolamine (MDEA) and 2-amino-2-methyl-1-propanol (AMP) have been measured at (288, 293, 298, 303, 308, 313, 318, 323, 328, and 333) K. The total amine mass fraction in all solutions was kept at 30 % in view of recent interest in using concentrated amine solutions in gas treating. Correlations for the density and viscosity of the ternary mixtures are presented as a function of temperature and amine concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
68
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 20 publications
2
68
0
1
Order By: Relevance
“…The average absolute deviations of the measurements are 0.07% for densities, 0.22% for viscosities, and 0.31% for surface tensions. The measured data of the physical properties in this work are in good agreement with the data of literature [10,15,16]. Thus, this work can validate the measurement procedures and experimental data.…”
Section: Validation For Methods and Procedures Of Measurementssupporting
confidence: 89%
See 2 more Smart Citations
“…The average absolute deviations of the measurements are 0.07% for densities, 0.22% for viscosities, and 0.31% for surface tensions. The measured data of the physical properties in this work are in good agreement with the data of literature [10,15,16]. Thus, this work can validate the measurement procedures and experimental data.…”
Section: Validation For Methods and Procedures Of Measurementssupporting
confidence: 89%
“…These are shown in Table 2. Measured values were compared with literature values [10,15,16]. The average absolute deviations of the measurements are 0.07% for densities, 0.22% for viscosities, and 0.31% for surface tensions.…”
Section: Validation For Methods and Procedures Of Measurementsmentioning
confidence: 94%
See 1 more Smart Citation
“…The most industrially used alkanolamines include: mono-ethanolamine (MEA), di-ethanolamine (DEA), and N -methyldiethanolamine (MDEA) [1]. Recently, sterically hindered amines are proposed as potential solvents for acid gas removal due to their unique cyclic structure and high CO 2 loading [2][3][4][5][6]. The investigated solvent in this paper, 2-amino-2-hydroxymethyl-1,3-propanediol (AHPD) is also a sterically hindered amine [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition it has been reported that (aqueous) AMP is easier to regenerate compared to primary and secondary amines [2][3][4] and that aqueous solvent systems containing blended amines require lower energy during regeneration when AMP is a component. Thus, many reports on the physical properties of aqueous AMP [5][6][7][8] and aqueous amine blends containing AMP [9][10][11][12][13] that are deemed useful in the design of processes and equipment systems for CO 2 absorption have been made available in the technical literature. Likewise, data on (vapour + liquid) equilibria [14][15][16] and kinetics [17,18] and mass transport [19][20][21][22] of CO 2 absorption in blended alkanolamines containing AMP have also been reported.…”
Section: Introductionmentioning
confidence: 99%